Evaluation of the effect of the COVID-19 pandemic on the all-cause, cause-specific mortality, YLL, and life expectancy in the first 2 years in an Iranian population—an ecological study - Pirayesh, Zahra; Riahi, Seyed Mohammad; Bidokhti, Ali; Kazemi, Toba (Frontiers in Public Health, 2023)
Background: COVID-19 pandemic resulted in excess mortality and changed the trends of causes of death worldwide. In this study, we investigate the all-cause and cause-specific deaths during the COVID-19 pandemic (2020COVID-19 pandemic ( -2022) ) compared to the baseline (2018-2020), considering age groups, gender, place of residence, and place of death in south Khorasan, east of Iran Methods: The present ecological study was conducted using South Khorasan Province death certificate data during 2018-2022. The number of death and all-cause and cause-specific mortality rates (per 100,000 people) were calculated and compared based on age groups, place of residence, place of death, and gender before (2018)(2019)(2020) and during the COVID-19 pandemic (2020)(2021)(2022). We also calculated total and cause-specific years of life lost (YLL) to death and gender-specific life expectancy at birth.